129 Does the Index Finger to Ring Finger Ratio (2D:4D) Affect Sexual Functionality in Infertile Japanese Males?. (1st May 2022) - Yamasaki, K; Iwamoto, T; Uchida, M; Ihana, T; Kariya, F; Konishi, S
ABSTRACT: Introduction: During the prenatal period, sex hormones lead to permanent organizational effects on the brain and behavior, which are different from direct and reversible activational effects. The ratio of the lengths of the second and fourth digits (2D:4D) has been identified as a marker of prenatal androgen levels. In addition, 2D:4D has been shown to relate to sexual dimorphism (i.e., lower 2D:4D in males) as well as many sexually dimorphic physical traits such as penile and breast sizes and behavioral traits such as addiction. In this study, we investigated the relationship between 2D:4D and sexual functionality. Methods: In total, 198 patients who visited the male infertility clinics at either Sanno Hospital or Tsukuba Gakuen Hospital in Japan between September 2020 and March 2021 were included in this study. After obtaining written informed consent, the patients were required to complete a questionnaire (see below), following which, both their palms were scanned with image scanners. The lengths of the second and fourth digits of both hands were measured from the scanned images using a software (Matlab Image Viewer). The ratio between the second and fourth digits was calculated for the left (L-2D:4D) and right (R-2D:4D) hands separately. The questionnaire comprised two parts: (1) questions about lifestyle factors (sleep duration, exercise, smoking, and alcohol consumption), age, height, and body weight and (2) the International Index of Erectile Function (IIEF-15) score, which comprises five functional domains (A, erectile function; B, orgasmic function; C, libido; D, sexual satisfaction; and E, total satisfaction). Pearson's correlation coefficients were calculated for each IIEF domain score and R-2D:4D or L-2D:4D. Linear regression models were used to determine associations between IIEF domain scores and R-2D:4D or L-2D:4D while adjusting for age, BMI, logged concentrations of serum hormones (follicle-stimulating hormone, luteinizing hormone, prolactin, testosterone, and estradiol), and lifestyle factors. Serum hormone concentrations were measured using a chemiluminescent immunoassay. All statistical analyses were performed using R software, ver. 3.6.0. The level of statistical significance was set to p<0.05. Results: The mean (SD) value of L-2D:4D was 0.938 (0.031), and that of R-2D:4D was 0.950 (0.031). L-2D:4D showed significant positive correlations with the IIEF domain B (r=0.139, p=0.049) and domain C (r=0.160, p=0.023) but not with the domains A, D, or E. R-2D:4D showed no significant correlations with any domain score. After adjusting for potential confounders, no significant associations were observed between IIEF domain scores and R-2D:4D, whereas only domain B was significantly positively associated with L-2D:4D (coefficient 12.9, 95% confidence interval 0.01–25.7, p=0.049). Conclusions: We measured, for the first time, the 2D:4D of infertile Japanese males and examined its relationship with sexual functionality. However, its clinical significance is currently unknown. Clinical research on whether 2D:4D is associated with sexual function and spermatogenesis has just begun, and further studies are warranted in this regard. Disclosure: Work supported by industry: no.